Design Modification of Flight Information Display System Simulator Based on Web Using Text To Speech at Aviation Polytechnic of Surabaya - Aswandi; Irfansyah, Ade; Ratna Sari, Dewi (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2025)
The limited learning facilities at the Surabaya Aviation Polytechnic have resulted in the understanding and operation of the Flight Information Display System (FIDS) remaining largely theoretical, with minimal practical application. This condition creates a gap between the practical competencies required by students and the available learning resources, highlighting the academic urgency for more interactive and applicable learning media. This study aims to design and develop a web-based FIDS simulator integrated with a Text to Speech (TTS) feature, providing not only visual information but also audio outputs similar to real airport systems. The development process employed the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) using Visual Studio Code and XAMPP. System evaluation included white box and black box testing to assess functionality, as well as validation by media experts (3 lecturers) and users (30 students) through a usability questionnaire. The results demonstrated that all system functions operated as designed, while the validation process produced an average usability score of 87.6%, placing it in the “highly usable” category. The findings indicate that the web-based FIDS simulator with TTS integration successfully enhances interactivity and provides a learning experience that closely simulates real operational conditions. Scientifically, this study contributes to the development of simulation-based learning media in aviation vocational education and may serve as a reference for similar system development in other aviation institutions. Practically, the system can be implemented both as an independent learning tool and as an integrated laboratory resource, supporting students in achieving competencies more effectively.